2020
DOI: 10.7717/peerj.9895
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic fungi decreaseRhizoctoniadisease in potato in field conditions

Abstract: Rhizoctonia potato disease is widespread in the world and causes substantial yield and quality losses in potato. This study aimed to evaluate the efficacy of entomopathogenic fungi Metarhizium robertsii and Beauveria bassiana in the inhibition of potato Rhizoctonia complex disease. The efficacy of the entomopathogenic fungi M. robertsii and B. bassiana in the defense of potato against Rhizoctonia disease (stem cancer, black scrulf and other forms of manifestation on tubers) was estimated under field conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 79 publications
5
27
0
Order By: Relevance
“…It is important to note that the low level of potato colonization by entomopathogenic fungi under their natural load does not exclude the benefits for plants following the artificial introduction of the fungi into agrosystems. We showed previously [ 14 ] that the pre-planting treatment of tubers with M. robertsii and B. bassiana suspensions (5 × 10 7 conidia/mL) led to successful endophytic colonization of potato roots under field conditions (32–47% fungi-positive plants in the flowering period). Potato growth stimulation, immunity activation, and a decrease in Rhizoctonia diseases were also registered in treated plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the low level of potato colonization by entomopathogenic fungi under their natural load does not exclude the benefits for plants following the artificial introduction of the fungi into agrosystems. We showed previously [ 14 ] that the pre-planting treatment of tubers with M. robertsii and B. bassiana suspensions (5 × 10 7 conidia/mL) led to successful endophytic colonization of potato roots under field conditions (32–47% fungi-positive plants in the flowering period). Potato growth stimulation, immunity activation, and a decrease in Rhizoctonia diseases were also registered in treated plants.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that M. brunneum may mitigate nutrient deficits in soil by improving plant productivity. We showed in previous work [ 14 ] that treating potato tubers pre-planting with Beauveria bassiana and Metarhizium robertsii conidia led to a decrease in Rhizoctonia disease and stimulation of plant growth under field conditions. Thus, work on the interactions between entomopathogenic fungi and potato plants was conducted either in the laboratory in sterile substrates or under field conditions after introducing the fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Strains of Be. Bassiana have also provided potato with protection from Rhizoctonia solani [72] and tomato with protection from Fusarium oxysporum f. sp. lycopersici [73], Rhizoctonia solani and Pythium myriotylum [51].…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoctonia solani Kuhn is the most destructive potato disease, causing stem canker and black scurf (Woodhall et al, 2007;Daami-Remadi, Zammouri & Mahjoub, 2008;Das et al, 2014;Yang et al, 2017). In Western Siberia, the damage caused to potatoes by Rhizoctonia disease can reach 67-70.8% (Tomilova et al, 2020). One of the most common raspberry fungal diseases is spur blight caused by Didymella applanata (Niessl) Sacc.…”
Section: Introductionmentioning
confidence: 99%